Nursing stress and associated factors during covid-19 pandemic: findings of a cross-sectional study at tertiary hospitals in Bangladesh - Siddika, Ayesha; Islam, ANM Shamsul; Hossain, Mohammad Monir; Islam, Md Ziaul (Journal of Preventive and Social Medicine, 2024)
Background: The COVID-19 epidemic has posed an unparalleled obstacle to healthcare systems worldwide. Particularly in the pandemic period, nursing is seen as a demanding profession with high standards. This study was conducted to assess the level of nursing stress and to identify the factors related to high nursing stress among nurses working in dedicated COVID-19 hospitals. Methods: The cross-sectional study was conducted from selected three dedicated COVID-19 public hospitals in Dhaka city of Bangladesh named Dhaka Medical College Hospital, Shaheed Suhrawardy Medical College, and Hospital, Dhaka North City Corporation dedicated COVID-19 hospital from 1st July 2021 to 30th June 2022. Total respondents were 368 who had working experience more than 6 months in above mentioned hospitals. Data were collected by face-to-face interview through pre-tested semi-structured questionnaire. Nursing stress was assessed by Nursing Stress Scale (NSS) and categorized as low (≤39), moderate (40-62), and high (>62) stress score. Data analysis was carried out by using SPSS version 26. Results: The mean age of the respondents was 30.8±7.8 years, wherein highest number of respondents were in age group 20-30 years (50.3%). Among the respondents 86.7% were female, 83.4% were married and average monthly family income Tk. 53839±28587.7 taka. About 63% respondents had diploma degrees, 77.4% worked in different wards, and mean working hour per week was 51.9±5.6 hour. Overall, maximum 52.2% had moderate stress, while 39.4% had high stress and only 8.4% had low stress. Age >30 years, male, marital status, working place, having senior citizen (>60 years) and feeling stressed for isolation were the significant risk factors for having high stress level. Conclusion: Occupational health education, training programs, stress relieving programs, and motivational programs must be implemented in tertiary level hospitals. Special attention should be given on older aged married male nurses, having elderly family members and feeling stressed for isolation. JOPSOM 2023; 42(1):54-61